Gamifications: Lexical and trajectory image methods as cognitive intervention in numeracy - Siti Rahaimah Ali; Anida Sarudin; Raja Noor Farah Azura; Mohamad Zuria Farhana (International Journal of Evaluation and Research in Education (IJERE), 2022)
This paper describes a study with the goal of exposing children to gamification activities in teaching and learning numeracy based on the lexical method by implementing a trajectory image (image representator). Early childhood learning difficulties in understanding abstract and symbolic numerical concepts and procedures have been identified as an issue that needs to be addressed and acted as a starting point in the effort to shape the transformation of early childhood mathematics both in teaching and learning. Therefore, this study would like to inspect the role played by language as the medium used in translating the concept of numeracy whether it is applied contextually or in a variety of contexts. The respondents selected for this study were 10 teachers and 50 preschool children and a numeracy module instrument based on the numeracy comprehension level model framework (MPKN) was chosen and applied to students by using lexical and image methods called trajectory image or image representator. Findings have shown that the understanding of preschool children related to previous aspects of numeracy is still at level 1 and level 2. It clearly stated that children are still unable to grasp the concept of numeracy in detail. This study has introduced the MPKN and LexsMath gamification products that have successfully provided a clear understanding to children regarding the in-depth understanding of numeracy aspects from level 1 to level 4 and also have shed some light on more effective teaching methods that can be employed in the aspect of numeracy teaching and learning.